Green Economy as a Paradigm of Sustainable Development of the Republic of Kazakhstan - Kalikov, Maxat; Uteyev, Bakytnur Zh.; Khajieva, Aiman; Torekulova, Uldana A. (Journal of Environmental Accounting and Management, 2026)
The aim of the paper is to analyse the green economy as a paradigm of sustainable development of the Republic of Kazakhstan. The paper found that the use of alternative energy is an integral part of the development of the green economy. It is determined that the total capacity of renewable energy sources in the world until 2024 will increase by 50%. The necessary elements of the transition to the green economy are the development of new financial instruments, namely, payments for ecosystem services, green banking, stocks and bonds, markets for the sale of intellectual property in environmental technologies.